PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, DAN TINGKAT KEMISKINAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN MIMIKA - Gratsianus W. P. Mare; Frits Fransiskus Layanan, Demianus Yohanes Rahayaan (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the influence of Local Original Revenue, Equalization Funds, and Poverty Levels on Economic Growth in Mimika Regency. The research method used is an associative method. The data collection technique used by the researcher is a documentation technique in the form of taking data that has been published by the Central Bureau of Statistics and Journal Publications. The analytical tool used in this study is multiple linear regression with the help of SPSS 25 software. The results of this study indicate that both individually and simultaneously, Local Original Revenue, Equalization Funds, and Poverty Levels do not have a significant effect on Economic Growth in Mimika Regency.